Should goodwill be amortised? Empirical evidence from UAE / Yousef Shahwan - Shahwan, Yousef (Accounting Research Institute (ARI) & Faculty of Accountancy, 2005)
Accounting for goodwill is one of the most controversial issues in financial reporting. This study provides empirical evidence on whether goodwill amortisation requirement is inappropriate. It analyses the information content of goodwill amortisation in the determination of firm’s market valuation by Emirates Financial Market Listed companies that clearly reported goodwill amortisation over the period 1990 to 2002 inclusive. Evidence suggests that there is a statistically insignificant association between equity market values and goodwill amortisation in the determination of firms’ market valuation, concluding that the UAE market does not perceive goodwill amortisation as having information content when valuing firms, and the use of standardised amortisation requirement may be inappropriate.